Language aggression in public debates on immigration - Musolff, Andreas (Benjamins current topics ;, 2019)
The global rise in the number, size and complexity of migration flows has not only resulted in an unprecedented flurry of debates and negotiations about how to deal with it through economic, social, and military policies but also in a huge increase in racist and xenophobic language use and discriminatory discourse. The expression of aggression and hatred in (anti-)immigration debates and its relationship to racism and its pseudo-justification lie at the center of this volume.00Its seven main contributions provide exemplary analyses of European and US debates that instrumentalize anti-immigrant attitudes: on the one hand among far-right populists in Cyprus, in Serbian and Croatian nationalism, and in the Hungarian government?s attempts at legitimizing immigration exclusion, and on the other hand in discourses associated with US-president Trump and his followers, including racists? tactical denial of racism. Methodologically, all studies pursue corpus-based Critical Discourse Analysis, with foci on lexical, figurative, argumentative and discourse-historical patterns. Together, they show the convergence of populist polemic strategies.